PENGARUH VIRAL MARKETING, BRAND AMBASSADOR, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN NATASHA SKINCARE DI KOTA BATAM - Artika Mulia Sari; Nur Elfi Husda (Prosiding, 2025)
Increasingly fierce business competition is driving companies to innovate in digital marketing strategies. One approach used is viral marketing, brand ambassadors, and building consumer trust to influence purchasing decisions. This study aims to determine whether influencer endorsements, customer reviews, and perceived quality influence purchasing decisions for Skintific products on TikTok Shop, both individually and collectively. A systematic and structured quantitative approach was used, located in Batu Aji District, Batam City. The population included all Natasha Skincare users in the area, and a sample of 100 people was determined using a purposive sampling method. Respondents were active users of Natasha Lightening Night Cream. Data were collected through a questionnaire and analyzed using multiple linear regression. Viral marketing has been proven effective in increasing purchase intention through the distribution of interactive content on social media. Brand ambassadors contribute to building a positive image and emotional attachment to the product. Consumer trust is formed from perceptions of quality, transparency, and previous experience, which strengthen the tendency to purchase. All three complement each other in forming stronger purchasing decisions